Contribution of Supervision of School Supervisor and School Quality Culture on Primary School’s Managerial Competence - Maskur, Maskur; Haryono, Haryono; Hidayah, Isti (Educational Management, 2018)
Supervision of school supervisor is one of the instruments in improving the quality of education at schools. An effective school has strong cultures with particular characteristics. An effective school also needs a leader who is expert in implementing school based management. This research was aimed to find out the amount of contribution of school supervisor’s supervision and school quality culture towards elementary school principals’ managerial competence in Kendal regency. This research used quantitative approach. The population of this research is all elementary school principals in Kendal regency. The sample was 50 elementary school principals randomly selected from 5 districts in Kendal regency, namely Brangsong district, Weleri district, Pageruyung district, Kaliwungu district and Kendal Kota district. Data collection was conducted by using Likert scale questionnaire. Data analysis was carried out by using multiple linear regression analysis. The result shows that there is a significant influence of school supervisor’s supervision on principals’ managerial competence. This scale shows the strong influence between the two variables. These include the rectification and improvement of teaching learning process, construction and development of curriculum, and schools’ teachers and staffs human resource development. The responses of the principal on the points reflected the process of supervision conducted by school supervisor on the leadership and the condition of school in which he is in charge. The second result shows that there is a significant influence of school quality culture on principals’ managerial competence. This scale shows the strong influence between the two variables. Things which are related to school quality culture includes principal’s roles, work’s situation and the giving of feedback. The response of the principal reflected the condition of quality culture in the school he leads. Then, the other result of the research shows that school supervisor’s supervision and school quality culture together have significant influence on principals’ managerial competence. The variable of principals’ managerial competence can be explained by the variable of school supervisor’s supervision and school quality culture. It means the increase or decrease of the principal’s managerial competence score can be predicted by the two independent variables.  Suggestions which can be given based on the result of this research are that school supervisors should maintain the supervision process on their supervised schools, the principals who have already had good managerial competence should maintain it by supporting the supervision of school supervisors and keeping the good school quality cultures. Meanwhile, the principals who have not had the good managerial competence should start to respond supervision of school supervisors seriously, do some rectifications at school, and create conducive school quality culture. Also, school teachers and staff should always support the supervision process and the good condition  of school quality culture so that effective school can be achieved.